2010
DOI: 10.1094/cchem-87-1-0050
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Enzyme Characterization of Small and Large Starch Granules Isolated from Two Maize Cultivars

Abstract: In this study, some morphological, physicochemical, and the initial characterization of the starch granule enzymes of blue and white maizes of small and large granules are described. Starch was isolated from blue and white maizes, and the small and large granules were separated. The efficiency of separation was higher in large granules than small of the blue maize starch. The amylose content was slightly greater (1.3%) in large granules than smaller in both starches studied. No differences in the average gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Similar results were reported for developing wheat (Meredith 1981;Morrison and Gadan 1987) and barley (McDonald et al 1991) starches and for mature wheat, triticale, and barley starches (Ao and Jane 2007;Liu et al 2007;Zeng et al 2011). It was reported that GBSSI has higher expression in large granules than in small granules in maize starches, which would explain the higher AAM content in the large granules (Utrilla-Coello et al 2010). That RC decreased in both A-and B-type granules during their development suggested an effect of the increasing AM content, which agreed with the finding that AM increased the defects in the crystalline lamellae .…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were reported for developing wheat (Meredith 1981;Morrison and Gadan 1987) and barley (McDonald et al 1991) starches and for mature wheat, triticale, and barley starches (Ao and Jane 2007;Liu et al 2007;Zeng et al 2011). It was reported that GBSSI has higher expression in large granules than in small granules in maize starches, which would explain the higher AAM content in the large granules (Utrilla-Coello et al 2010). That RC decreased in both A-and B-type granules during their development suggested an effect of the increasing AM content, which agreed with the finding that AM increased the defects in the crystalline lamellae .…”
Section: Discussionsupporting
confidence: 86%
“…Starch granules can be separated into different fractions according to their sizes (Ao & Jane, 2007;Chiotelli & Le Meste, 2002;Dhital, Shrestha, Hasjim, & Gidley, 2011;Kaur, Singh, McCarthy, & Singh, 2007;Noda et al, 2005;Singh & Kaur, 2004;Tang, Ando, Watanabe, Takeda, & Mitsunaga, 2001; Utrilla-Coello, Agama-Acevedo, de la Rosa, Rodríguez-Ambriz, & Bello-Pérez, 2010;Vasanthan & Bhatty, 1996). The properties of different size fractions can provide information on their applications in food and non-food industries (Dhital et al, 2011).…”
Section: Manymentioning
confidence: 99%
“…For normal starches with unimodal granule size distribution, amylose content and pasting viscosity increase and gelatinization temperature and hydrolysis degree decrease with increasing granule size (Dhital et al, 2011;Kaur et al, 2007;Noda et al, 2005;Singh & Kaur, 2004; http://dx.doi.org/10.1016/j.carbpol.2015.08.026 0144-8617/© 2015 Elsevier Ltd. All rights reserved. Utrilla-Coello et al, 2010). However, no work has investigated the effect of granule size on the properties of C-type starches.…”
Section: Manymentioning
confidence: 99%
“…Evidence of anthocyanin deposition, and the relationship with starch biosynthesis and structure are not clear. However, difference in amylose content, gelatinization parameters, and enzyme starch biosynthesis of small and large starch granules from white and blue maize has been reported 9. There are currently no studies about blue maize starch characterization, and with the knowledge of chemical, molecular, and structural composition, we can improve the products made with this grain which also as the characteristics of a functional food.…”
Section: Introductionmentioning
confidence: 99%